A solvent-controlled photoresponsive ionic hydrogen-bonded organic framework for encryption applications - Huang, Ming-Feng; Cao, Li-Hui; Zhou, Bin (Chemical communications (Cambridge, England), 2024)
Two novel ionic hydrogen-bonded organic frameworks ( iHOF-17 and iHOF-18 ) were obtained by integrating organosulfonic acids with amidine salts. Among them, iHOF-18 exhibits fast, reversible, and high-contrast UV-induced photochromic properties, and this property is solvent-controlled. This work provides valuable insights for designing advanced anti-counterfeiting techniques and encryption applications. An ionic hydrogen-bonded organic framework exhibits fast and reversible photochromic properties. Benefiting from the stimuli-responsive property, information encryptions and decryptions integrated with photoresponsivity are successfully designed.